2008
DOI: 10.1080/09588220701865474
|View full text |Cite
|
Sign up to set email alerts
|

Adventures in the blogosphere: from blog readers to blog writers

Abstract: This paper reports on a year-long project in which students participated as both readers and writers of blogs. Specifically, this study examines the steps students progress through while reading and writing blogs, students' reactions to blogging, and how self-expression is characterised in the blogosphere. Data from student blogs, reports, and focus group interviews suggest that this project fostered both ownership and creativity; allowed students to experiment with language; facilitated expression in a relaxe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
123
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 238 publications
(139 citation statements)
references
References 10 publications
7
123
0
3
Order By: Relevance
“…Blogs promoted constructivist learning, provided reinforcement and increased accountability (Ducate & Lomicka, 2008). Moreover, teachers who gave their students the chance to engage in blog-based learning were readily able to track their individual students' learning progress and thus overall course performance (Wheeler & Lambert-Heggs, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…Blogs promoted constructivist learning, provided reinforcement and increased accountability (Ducate & Lomicka, 2008). Moreover, teachers who gave their students the chance to engage in blog-based learning were readily able to track their individual students' learning progress and thus overall course performance (Wheeler & Lambert-Heggs, 2009).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, teachers who gave their students the chance to engage in blog-based learning were readily able to track their individual students' learning progress and thus overall course performance (Wheeler & Lambert-Heggs, 2009). Here, blogs worked as indicator or alternative assessment tool and some studies reported that blogs are more appropriate in predicting the learning performance than traditional coursework (Ducate & Lomicka, 2008). Therefore, it can be observed that from a pedagogical point of view, blogs enhance education by encouraging reflective practice in students: they help the students to take the leadership and engage responsibly in executing the learning activities.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Many authors offer some useful ideas on how to use blogs in English language teaching, e.g. for practice in reading and writing (Zhang, 2009, Ducate and Lomicka, 2008, Ward, 2004, for study in literature (Morrison, 2008), to foster reflection and social interaction and cooperation (Ray & Hocutt, 2006), as a journal run by teachers and students, providing space for comments, reactions and reflections on what has been done in class to be published; an online space to exchange intercultural projects and represent an online community of teachers and students (Dieu, 2004), etc.…”
Section: Blogs In Efl Educationmentioning
confidence: 99%
“…Many teachers are becoming progressively aware of the potential profits of blogs in education as tools for collaboration among students. However, the strategy of using blogs is still widely unexplored (Lamy & Hampel, 2007;Baniabdelrahman, Bataineh & Bataineh, 2007), and research into the use of blogs for increasing language skill is still limited (Ducate & Lomicka, 2008;Kuteeva, 2011).…”
Section: Introductionmentioning
confidence: 99%